'Life with a device': the octogenarians' experiences with an implantable cardioverter-defibrillator—a qualitative study. (30th April 2021) - Wising, Jenny; Mattsson, Gustav; Rambaree, Komalsingh; Willmer, Mikaela; Wallhagen, Marita; Magnusson, Peter
Abstract: Aims: Implantable cardioverter-defibrillator (ICD) treatment has expanded due to its effectiveness. However, there are concerns about complications, and use in the most elderly has been questioned. There is scarce data on qualitative aspects regarding experiences of living with an ICD among patients above the age of 80 years. The aim of this study was to explore octogenarians' experience, knowledge, and attitude of living with an ICD. Method and results: We used semi-structured interviews to collect data from 20 patients, aged 80–89 years (90% men). The data were then structured and analysed through deductive thematic analysis network approach using the ATLAS.ti v.8.4 software. The framework of the analysis was based on the Successful Aging Theory. Three main themes emerged regarding the patients' experiences: Life goes on; Their Health, The Janus-Faced Device; Their attitudes, and Mind the gap ; Their knowledge . None of the octogenarians regretted receiving their ICD, instead, they presented with feelings such as gratitude towards the device. However, a lack of knowledge about the devices was expressed, which can be a risk for potential complications, in turn causing suffering and unnecessary concerns. Conclusion: Overall, the ICD did not pose a threat towards successful ageing. It was mainly considered a life-saving device. However, the lack of knowledge might hinder informed choices close to death and contribute to ethical dilemmas when deactivation of the ICD is a reasonable option.